On the classification of 2 (1 )n n ï‚³ ï€« ï€dimensional non-linear Klein-Gordon equation via Lie and Noether approach - Jhangeer, Adil; Al-Mufadi, Fahad (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
A complete group classification for the Klein-Gordon equation is presented. Symmetry generators, up to equivalence transformations, are calculated for each f (u) when the principal Lie algebra extends. Further, considered equation is investigated by using Noether approach for the general case n ï‚³ 2. Conserved quantities are computed for each calculated Noether operator. At the end, a brief conclusion is presented.